Writing Handwritten Messages on a Small Touchscreen - Kienzle, Wolf; Hinckley, Ken (ACM MobileHCI, 2013)
We present a method for composing handwritten messages on a small touchscreen device. A word is entered by drawing overlapped, screen sized letters on top of each other. The system does not require gestures or timeouts to delimit characters within a word—it automatically segments the overlapping strokes and renders the message in real-time as the user is writing. The auto-segmentation algorithm was designed for practicality; it is extremely simple, requires only public domain data for training, and runs very fast on low-power devices. Drawings may also be included with the text. Experimental data indicates the effectiveness of our system, even for novice users.